2022
DOI: 10.3390/ijerph19116755
|View full text |Cite
|
Sign up to set email alerts
|

Education for Sustainable Development and Meaningfulness: Evidence from the Questionnaire of Eudaimonic Well-Being from German Students

Abstract: Education for Sustainable Development (ESD, SDG 4) and human well-being (SDG 3) are among the central subjects of the Sustainable Development Goals (SDGs). In this article, based on the Questionnaire for Eudaimonic Well-Being (QEWB), we investigate to what extent (a) there is a connection between EWB and practical commitment to the SDGs and whether (b) there is a deficit in EWB among young people in general. We also want to use the article to draw attention to the need for further research on the links between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…After analyzing self-report questionnaires, they concluded that this relationship "is not merely a matter of social desirability, but rather a matter of meaning: acting sustainably is perceived as a moral choice and thus as a meaningful course of action, which can elicit positive emotions" [72] (p. 8). Klement and Terlau [73] concluded that college students who were involved in (extra)curricular activities in favor of sustainable development tended to report higher eudaimonic well-being related to self-discovery and meaning in life than a control group. Another study underlined the prominent role of environmental hope in promoting both PEB and the well-being of high school students.…”
Section: Construction Of Meaning and Pebmentioning
confidence: 99%
“…After analyzing self-report questionnaires, they concluded that this relationship "is not merely a matter of social desirability, but rather a matter of meaning: acting sustainably is perceived as a moral choice and thus as a meaningful course of action, which can elicit positive emotions" [72] (p. 8). Klement and Terlau [73] concluded that college students who were involved in (extra)curricular activities in favor of sustainable development tended to report higher eudaimonic well-being related to self-discovery and meaning in life than a control group. Another study underlined the prominent role of environmental hope in promoting both PEB and the well-being of high school students.…”
Section: Construction Of Meaning and Pebmentioning
confidence: 99%